Their fathers' daughters : Hannah More, Maria Edgeworth, and patriarchal complicity - Kowaleski-Wallace, Elizabeth, 1954- (Oxford University Press, 1991)
Current feminist theory has developed powerful explanations for some women writers' rebellion against patriarchy. But other women writers did not rebel; rather, they supported and celebrated patriarchy. Examining the lives and selected works of two late eighteenth-century writers, Hannah More and Maria Edgeworth, this book explores what it means for a woman writer to identify with her father and the patriarchal tradition he represents. Kowaleski-Wallace exposes the psychological, social, and historical factors that motivated such an identification, and reveals the consequences that result from.